Socio-psychological view on the modern charismatic movement - Vita Volodymyrivna Tytarenko (Українське Pелігієзнавство, 2001)
The emergence and activity of neo-religious groups, to which we also refer to charismatic churches, is a manifestation of one of the global trends of modern religious life-traditional encounter with a new, still unknown. Therefore, it is quite natural that this contact within the framework of the modern charismatic movement - this complex, multifaceted phenomenon, requires a comprehensive study, in particular philosophical, sociological, religious, theological, etc. No less relevant is the psychological approach, due to the importance of personal religious experiences in the life of the person.